Phosphorylation of CDC25A on SER283 in late S/G2 by CDK/cyclin complexes accelerates mitotic entry. Issue 20 (17th October 2016) - Mazzolini, Laurent; Broban, Anaïs; Froment, Carine; Burlet-Schiltz, Odile; Besson, Arnaud; Manenti, Stéphane; Dozier, Christine
ABSTRACT: The Cdc25A phosphatase is an essential activator of CDK-cyclin complexes at all steps of the eukaryotic cell cycle. The activity of Cdc25A is itself regulated in part by positive and negative feedback regulatory loops performed by its CDK-cyclin substrates that occur in G1 as well as during the G1/S and G2/M transitions. However, the regulation of Cdc25A during G2 phase progression before mitotic entry has not been intensively characterized. Here, we identify by mass spectrometry analysis a new phosphorylation event of Cdc25A on Serine283. Phospho-specific antibodies revealed that the phosphorylation of this residue appears in late S/G2 phase of an unperturbed cell cycle and is performed by CDK-cyclin complexes. Overexpression studies of wild-type and non-phosphorylatable mutant forms of Cdc25A indicated that Ser283 phosphorylation increases the G2/M-promoting activity of the phosphatase without impacting its stability or subcellular localization. Our results therefore identify a new positive regulatory loop between Cdc25A and its CDK-cyclin substrates which contributes to accelerate entry into mitosis through the regulation of Cdc25A activity in G2.